Penilaian Degradasi Lahan Gambut Pada Beberapa Land Use di Desa Batang Duku Kecamatan Bukit Batu Kabupaten Bengkalis, Riau - Fajriyantie, Dessy; Wawan, Wawan; Budijono, Budijono (Pelantar Press, 2024)
Peatlands are fragile, so their use must be carefully managed to prevent land degradation and ecosystem damage. Currently, peatlands in Batang Duku Village, Bukit Batu Subdistrict, Bengkalis Regency, Riau, have been utilized for various land uses, but it is not yet known which land areas are not degraded. Therefore, this study aims to determine whether the peatland use in the research location has been degraded or not This research was conducted using a survey method. The research location was determined through purposive sampling, while the sampling points were selected using systematic sampling. In this study, there are four types of peatland use: horticulture, oil palm plantations, rubber plantations, and shrubland, with three observation points established for each land use. Peatland degradation was assessed using a comparative method. The results of the peatland degradation analysis for the four land uses in Batang Duku, Bukit Batu, Bengkalis, Riau, indicate that, according to PP No. 71/2014 and PP No. 57/2016, the peatlands are classified as degraded. Similarly, according to PP No. 150/2000, the peatlands are also classified as degraded. However, when the degradation analysis refers to BBSDLP (2018), the peatlands are classified as not degraded (very heavy category).